2018
DOI: 10.15252/emmm.201708307
|View full text |Cite
|
Sign up to set email alerts
|

The AMPK agonist 5‐aminoimidazole‐4‐carboxamide ribonucleotide (AICAR), but not metformin, prevents inflammation‐associated cachectic muscle wasting

Abstract: Activation of AMPK has been associated with pro‐atrophic signaling in muscle. However, AMPK also has anti‐inflammatory effects, suggesting that in cachexia, a syndrome of inflammatory‐driven muscle wasting, AMPK activation could be beneficial. Here we show that the AMPK agonist AICAR suppresses IFNγ/TNFα‐induced atrophy, while the mitochondrial inhibitor metformin does not. IFNγ/TNFα impair mitochondrial oxidative respiration in myotubes and promote a metabolic shift to aerobic glycolysis, similarly to metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(89 citation statements)
references
References 95 publications
7
76
1
Order By: Relevance
“…To identify the network of mRNAs that associate with HuR during muscle wasting, we used C2C12 myotubes treated with or without IFNγ/TNFα to perform RNA immunoprecipitation (RIP) coupled to cDNA microarray experiments using an anti-HuR monoclonal antibody (3A2) (12,23,24,27). This in vitro cell model of muscle wasting is routinely used to mimic the effects of cytokines on muscle fibers, as seen during cachectic conditions (7,12,28,29) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To identify the network of mRNAs that associate with HuR during muscle wasting, we used C2C12 myotubes treated with or without IFNγ/TNFα to perform RNA immunoprecipitation (RIP) coupled to cDNA microarray experiments using an anti-HuR monoclonal antibody (3A2) (12,23,24,27). This in vitro cell model of muscle wasting is routinely used to mimic the effects of cytokines on muscle fibers, as seen during cachectic conditions (7,12,28,29) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…2D). Using the Lewis lung carcinoma (LLC) model of cancer inflammation-induced muscle wasting (29,32), we observed that the genetic ablation of HuR protected muHuR-KO mice from the LLC tumor-induced muscle loss that is normally observed in the control mice ( Fig. 2 E and F).…”
Section: Hur Promotes Stat3 Expression During Muscle Wasting Both In mentioning
confidence: 99%
“…Activators of AMPK, inflammatory www.nature.com/scientificreports www.nature.com/scientificreports/ cytokines and metformin, decreased the rate of protein synthesis. However, treatment with AICAR and A-769662, which activate AMPK, restored the levels of phosphorylated S6K and S6 proteins, which are markers of protein synthesis 32 . These findings suggested that AMPK activation induced by AICAR and A-769662 could restore protein synthesis in skeletal muscle.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, TGF-β1 mRNA and protein expression are significantly increased in skeletal muscles of humans and mice with ALS, and because of this characteristic, TGF-β1 could be used as a muscle biomarker for ALS disease 10 . Previous studies have shown that AMPK activation can prevent muscle wasting induced by inflammation through inhibition of the iNOS/NO pathway 32 . Therefore, we investigated whether hUCB-MSCs could inhibit the iNOS/NO pathway and found that hUCB-MSCs could prevent muscle atrophy by reducing nitrite concentration and iNOS protein levels in in vitro and in vivo studies ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Third, dorsomorphin was not a specific AMPK inhibitor which also inhibits BMP signaling and the VEGF type 2 receptor [36][37][38]. Notwithstanding its limitation, dorsomorphin was still used to inhibit AMPK in recent studies [39,40] since it remains the only small molecule that has been found to inhabit AMPK signaling [41]. However, it would be more specific to apply AMPK knockout mouse models to examine the specific role of AMPK in mediating the chondroprotective and pain relief effects of metformin; thus, future studies are still warranted to explore.…”
Section: Limitationsmentioning
confidence: 99%